Analysis of Economic Freedom, Foreign Direct Investment, and Economic Growth - Muhammad Lucky; Endraswati Hikmah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2024)
This research analyzes the relationship between economic freedom, foreign direct investment (FDI), and economic growth using the Vector Error Correction (VECM) model and the Granger causality test. Panel data from several free trade agreement countries in the Regional Comprehensive Economic Partnership (RPEC) for 1997 – 2022. VECM captures cointegration relationships and models short-term adjustments toward long-term balance. Meanwhile, the Granger causality test helps identify the direction of the causal relationship between economic freedom, FDI, and economic growth. Empirical results show a long-term but weak cointegration relationship between these variables in the short term. In addition, it was found that there is a two-way causality between economic freedom and economic growth, as well as between FDI and economic growth. These findings imply that policies encouraging economic freedom and attracting foreign investment can increase a country's economic growth. This research provides empirical insights into the important role of economic freedom and FDI in driving economic growth and related policy implications for creating an environment conducive to investment and sustainable economic growth.